Effects of protein levels and withdrawing supplemental protein on performance of growing and finishing steers - K.F. Harrison; G. Fink; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1975)
one growing trial and two finishing trials we used 264 steers. Rations containing 13.2% crude protein during the 105-day growing trial significantly (P<.05) improved rate of gain gain compared with 11.3% crude protein rations. Withdrawing supplemental protein at approximately 750, 850, or 950 pounds live weight did not significantly affect rate of gain; however, gain was slowest by steers without supplemental protein.
Keywords: Cattlemen& #x27; s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Protein; Steers; Gain